Clarification of Finger Millet (Eleusine coracana L.) Jand using Fining Agents - Karki, D. B.; Kharel, G. P. (Tribhuvan University Journal, 2013)
Finger millet (Eleusine coracana L.) was fermented using a defined fermentation starter to prepare millet jand (a traditional cereal-based alcoholic beverage). Millet jand was clarified using betonies, gelatin and tannin and the effect of bentonite on sensory and chemical characteristics were evaluated. Effects of holding time, temperature and jand acidity on clarification were also studied. Addition of bentonite at the rate of 3 g/L resulted in the best clarification without significantly affecting (p>0.05) the chemical and organoleptic properties of the clarified jand, whereas tannin and tannin-gelatin combination showed a negative effect on clarification. Jand acidity and bentonite concentration had a significant effect (p<0.05) on clarification. Bentonite, when added to pasteurizedand gravity settled jand, showed an adverse effect on clarification. Holding of bentonite treated jand beyond 3 days at room temperature (29±1ºC) did not improve clarification. Similarly, holding of bentonite treated sample under refrigeration (5±1°C) did not improve clarity compared to room temperature held sample. It was concluded that bentonite could be a promising fining agent in the clarification of millet jand without sacrificing quality.